A Single Dose Oral Azithromycin versus Intramuscular Benzathine Penicillin for the Treatment of Yaws-A Randomized Non Inferiority Trial in Ghana. - Cynthia Kwakye-Maclean; Nsiire Agana; John Gyapong; Priscilia Nortey; Yaw Adu-Sarkodie; Esther Aryee; Kingsley Asiedu; Roland Ballard; Fred Binka (PLoS Neglected Tropical Diseases)
Background Yaws is a treponemal infection that was almost eradicated fifty years ago; however, the disease has re-emerged in a number of countries including Ghana. A single-dose of intramuscular benzathine penicillin has been the mainstay of treatment for yaws. However, intramuscular injections are painful and pose safety and logistical constraints in the poor areas where yaws occurs. A single center randomized control trial (RCT) carried out in Papua New Guinea in 2012 demonstrated the efficacy of a single-dose of oral azithromycin for the treatment of yaws. In this study, we also compared the efficacy of a single oral dose of azithromycin as an alternative to intramuscular benzathine penicillin for the treatment of the disease in another geographic setting. Methodology We conducted an open-label, randomized non-inferiority trial in three neighboring yaws-endemic districts in Southern Ghana. Children aged 1-15 years with yaws lesions were assigned to receive either 30mg/kg of oral azithromycin or 50,000 units/kg of intramuscular benzathine penicillin. The primary end point was clinical cure rate, defined as a complete or partial resolution of lesions 3 weeks after treatment. The secondary endpoint was serological cure, defined as at least a 4-fold decline in baseline RPR titre 6 months after treatment. Non- inferiority of azithromycin treatment was determined if the upper bound limit of a 2 sided 95% CI was less than 10%. Findings The mean age of participants was 9.5 years (S.D.3.1, range: 1-15 years), 247(70%) were males. The clinical cure rates were 98.2% (95% CI: 96.2-100) in the azithromycin group and 96.9% (95% CI: 94.1-99.6) in the benzathine penicillin group. The serological cure rates at 6 months were 57.4% (95% CI: 49.9-64.9) in the azithromycin group and 49.1% (95% CI: 41.2-56.9) in the benzathine penicillin group, thus achieving the specified criteria for non-inferiority. Conclusions A single oral dose of azithromycin, at a dosage of 30mg/kg, was non-inferior to a single dose of intramuscular benzathine penicillin for the treatment of early yaws among Ghanaian patients, and provides additional support for the WHO policy for use of oral azithromycin for the eradication of yaws in resource-poor settings. Trial registration Pan African Clinical Trials Registry PACTR2013030005181 http://www.pactr.org/.